2014
DOI: 10.3762/bjoc.10.86
|View full text |Cite
|
Sign up to set email alerts
|

Visible-light-induced, Ir-catalyzed reactions of N-methyl-N-((trimethylsilyl)methyl)aniline with cyclic α,β-unsaturated carbonyl compounds

Abstract: Summary N-Methyl-N-((trimethylsilyl)methyl)aniline was employed as reagent in visible-light-induced, iridium-catalyzed addition reactions to cyclic α,β-unsaturated carbonyl compounds. Typical reaction conditions included the use of one equivalent of the reaction substrate, 1.5 equivalents of the aniline and 2.5 mol % (in MeOH) or 1.0 mol % (in CH2Cl2) [Ir(ppy)2(dtbbpy)]BF4 as the catalyst. Two major reaction products were obtained in combined yields of 30–67%. One product resulted from aminomethyl radical addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…Subsequent oxidation and deprotonation give the corresponding 1,2,3,4-tetrahydroquinoline derivatives. Similar reactions under modified reaction conditions have been reported by several groups. , …”
Section: Addition To Unsaturated Bondssupporting
confidence: 88%
“…Subsequent oxidation and deprotonation give the corresponding 1,2,3,4-tetrahydroquinoline derivatives. Similar reactions under modified reaction conditions have been reported by several groups. , …”
Section: Addition To Unsaturated Bondssupporting
confidence: 88%
“…The low solubility of the commonly used ruthenium catalyst [Ru(bpy) 3 Cl 2 ] ( 2 ; bpy=2,2′‐bipyridine) in this solvent, let us look for alternative catalysts to be tested in possible radical‐addition reactions. Based on earlier work, the iridium complex [Ir(ppy) 2 (dtbbpy)]BF 4 ( 3 ; ppy=phenylpyridyl, dtbbpy=4,4′‐di‐ tert ‐butyl‐2,2′‐bipyridine) seemed to be a good choice, and it was studied whether addition reactions to Michael acceptors could be performed. We now disclose details of our studies, which revealed that 3‐alkylidene indolin‐2‐ones are readily attacked by a variety of radicals generated from α‐trimethylsilyl (TMS) methyl‐substituted amines, and that moderate to good enantioselectivity values can be achieved in this transformation.…”
Section: Methodsmentioning
confidence: 99%
“… 6 Upon single electron transfer (SET) induced oxidation of an alkylamine, the resulting amine radical cation is known to undergo further reactions, with some of the possible pathways highlighted in Scheme 1a . 7 Commonly, α-aminoalkyl radicals are accessed through deprotonation of the α-C-atom following amine oxidation via SET. Alternatively, they can be afforded through homolytic cleavage of the α-C–H bond by a hydrogen atom transfer catalyst.…”
Section: Introductionmentioning
confidence: 99%